Kepastian Hukum Eksekusi Dan Pembatalan Putusan Arbitrase Syariah Dalam Perspektif Politik Hukum - Ainun Najib (Jurnal Hukum IUS QUIA IUSTUM, 2019)
This study examines two main problems which are, firstly, to describe the juridical construction of granting the authority to execute and to annul an sharia arbitration award in the perspective of legal policy. Secondly, to provide the better alternatives for the development of national law in the future. This is a normative legal research, which studies the written legal sources to be analyzed by using both the statutory and conceptual approach. Through this study, it was concluded that first, legally, the granting of authority to carry out the execution and the annulment of the sharia arbitration award is still affected with dualism, which could lead to legal uncertainty. Second, it is necessary to synchronize the legislation regarding the authority to execute and to annul the sharia arbitration award to ensure the legal certainty, so that it will not conflict with one another. In the future, the execution and annulment of sharia arbitration should be placed in the Islamic Court, as they both apply the sharia principles.